Popular endeavour against tuberculosis?its instruments, methods, and results - McWeeney, E.J. (Statistical and Social Inquiry Society of Ireland, 1912)
It was on the 24th March, 1882, that Koch brought forward his famous paper, in which he described his discovery of the Tubercle Bacillus, before the Berlin Physiological Society. Twenty-five years have since rolled by, and we may now be said to have arrived at the Silver Jubilee of the Bacillus. The present would, therefore, seem a very appropriate time to review the results of the impetus imparted by Koch's genius to the study of this most widespread and fatal of human diseases, and endeavour to precise the directions in which future exertion may be most fruitfully employed.
Read April 19th, 1907
Keywords: Tuberculosis; Mortality rates; 314.15